Creating an Inclusive City in Bandung: The Role of Communities in Addressing Social Exclusion - Azrananda, Gaizka; S. Sitorus, Stephanie Margarettha; Sulistiyanto, Adissty Putri; Latief, Jasmin Anizah (Universitas Wijaya Kusuma Surabaya, 2025)
Transgender women in Indonesia frequently face social exclusion in various aspects of life, including education, employment, and access to healthcare. When associated with HIV/AIDS, their position becomes even more marginalized due to the double stigmatization attached to gender identity and health status. This study aims to describe the forms of social exclusion experienced by transgender women and to examine how Yayasan Srikandi Pasundan in Bandung serves as a safe and inclusive space for transgender individuals living with HIV/AIDS. Employing a descriptive qualitative approach, data were collected through in-depth interviews and literature review. The findings reveal that transgender women with HIV/AIDS experience exclusion through healthcare denial, social alienation, and limited access to basic rights. On the other hand, Yayasan Srikandi Pasundan plays an important role as an alternative space that not only provides health services but also fosters community solidarity and the restoration of collective dignity. This study highlights the importance of community-based support in addressing the layered marginalization faced by transgender women in realizing an inclusive city, where every individual, including marginalized groups, can access basic rights equally.Keywords: HIV/AIDS, social inclusion, policy, waria community, stigma